Pengaruh Dukungan Belajar oleh Orang Tua terhadap Minat Belajar Siswa Kelas VII SMP N 1 Kota Jambi - Agnes Christianto. S; Nelyahardi Gutji; Siti Amanah (Journal on Education, 2023)
Parents support has a great psychological influence on child learning activities. With the support of parents, children will be more active and more excited in learning because he knows that not herself alone to want to move forward, but their parents are so. The purpose of this study is to examine the effect of learning support by parents to students at home. The atmosphere of the house is less supportive in learning, students do not have their own space to learn, parents are not always ready to help students experience difficulty in learning. The research used in this research is quantitative research with survey method. The population in this study is the class of VII CSTP N 1 city Jambi which amounted to 118 students and consisted of 5 classes. Correlational analysis of data shows that there is a significant positive relationship between learning support by parents to the interest of learning students of class VII SMP Negeri 1 Jambi city. Based on the processing of data supporting learning by parents contribute to student learning interest. The amount of contribution (donations) variable x (support by parent) to the variable y (student learning interest). This shows that in addition to the support of learning by parents, there are other factors that affect student learning interest. Capital of learning support by parents are fairly positive with the interest of learning students of class VII SMP Negeri 1 Jambi city is strong enough. The picture of the quality of study of students of class VII SMP1 Jambi City is a correlation coefficient of 0.474 greater than Rapable 0.226. Variable X donations (learning support by parents) to Y (VIDEO study students) are 22.46% and the level of correlation included in the moderate or strong enough category.